The grammar of civil war : a Mexican case study, 1857-61 - Fowler, Will, 1966- (University of Nebraska Press, 2022)
"Will Fowler examines the grammar of the origin, process, and outcome of civil war, and uses the Mexican 1857-61 Civil War as its principal case study to answer the question of why civil wars are so violent"--